Gait physiotherapy with motor imagery in people with Parkinson’s disease: a protocol for randomized control GAITimagery trial - San Martín Valenzuela, Constanza; Ramírez Murcia, Esperanza; Aznar-Requena, Estela; García Sotolongo, Dalia; Rosas-Martín, Rebeca; Sánchez-Sánchez, M. Luz (Frontiers in Neurology, 2025)
IntroductionAccording to people with Parkinson’s disease (PD), gait impairments are the most disabling motor symptoms of PD. Recently, motor imagery (MI) has gained notoriety as a gait training technique due to the flexibility of its use, however, it has not been demonstrated that causes a superior effect when included in physiotherapy. This study aims to determine if gait training combined with MI has a greater effect on the gait of people with PD than just gait training.MethodsThe GAITimagery is designed as a double-blind, randomized control trial, including a convenience sample in 2 parallel groups (1:1) with two interventions of 2 sessions per week during 6-week and 8-week follow-up. The initial recruitment will be 88 participants with idiopathic PD and unimpaired cognition state, who will be randomly divided into two groups: GAITimagery (GiG) or the active control Gait group (GaG). Both will perform the same gait exercises but only GiG will include MI training. Gait speed is the primary outcome, while Maximum gait speed (m/s) and Gait speed variability are the secondary results. The tertiary outcomes are related to Quality of life, Daily life activities, Freezing of gait, Balance, Mobility, and Gait performance measures to psychometrics and biomechanics instruments. All results will be measured at baseline (t0), post-training (t1), and follow-up assessment (t2) 8 weeks after finished physiotherapy programs.DiscussionThe GAITimagery program standardizes the application of MI exercises related to the improvement of parkinsonian gait at the same time that monitoring the vividness referred by the participants session by session. The effectiveness of this MI-exclusive program includes subjective and objective measurement tools to detect minimal changes after training. This still-to-be-finish study will support the therapeutic decisions on whether or not to allocate session time to imagery exercises depending on the effect size achieved and the comparison with a control gait training.